Falklands/malvinas war: 1st may 1982, the meteorology and naval battles that did not occur - Calearo, Daniel Sampaio; Cardoso, Camila de Souza (Ciência e Natura, 2018)
The Falklands/Malvinas war, was one of the most striking and surprising warlike events of modern history in many ways. One of the points that proved to be of great importance during the period in which they occurred fighting were extremely adverse weather conditions in the conflict area and their influence over the fighting. The work presented here deals with the case in which the two maritime forces (Argentine and British) composed of the aircraft carrier, were very close to a real confrontation. The situation could have changed the course of future clashes, but was thwarted by the third factor that acted in this relentlessly scenario, the weather. The presence of an anticyclonic system caused an unexpected calm in the winds in the south of the South Atlantic. This condition coupled with strategic factors that occurred simultaneously made it impossible to launch aircraft from carriers, especially in the case of the Argentine ship and thus the forces in combat had to back down waiting for a new ideal opportunity